2009
DOI: 10.1111/j.1096-3642.2009.00572.x
|View full text |Cite
|
Sign up to set email alerts
|

The morphology and systematics of Mammalodon colliveri (Cetacea: Mysticeti), a toothed mysticete from the Oligocene of Australia

Abstract: Mammalodon colliveri is an unusual toothed archaic mysticete (Cetacea) from the Upper Oligocene Jan Juc Formation of south-east Australia. The morphology of the holotype skull and postcrania are described in detail. Superimposed on the generally plesiomorphic archaeocete-like morphology of Mammalodon are subtle mysticete synapomorphies. Derived features of Mammalodon include a short and bluntly rounded rostrum, reduced premaxillae, and anterodorsally directed orbits. Within Mysticeti, this suite of features is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
218
2
14

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(246 citation statements)
references
References 141 publications
(592 reference statements)
12
218
2
14
Order By: Relevance
“…3). Our analyses showed that the organ receives neurovascular bundles that emerge from vestigial alveolar foramina of the mandibles, a structure that is homologous with the lower first incisor tooth socket of fossil 'toothed' mysticetes [14][15][16] . The presence and identity of these neurovascular bundles, which contain branches of the mandibular division of the trigeminal nerve, were confirmed by subsequent dissection of the same specimen.…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…3). Our analyses showed that the organ receives neurovascular bundles that emerge from vestigial alveolar foramina of the mandibles, a structure that is homologous with the lower first incisor tooth socket of fossil 'toothed' mysticetes [14][15][16] . The presence and identity of these neurovascular bundles, which contain branches of the mandibular division of the trigeminal nerve, were confirmed by subsequent dissection of the same specimen.…”
mentioning
confidence: 84%
“…The origin of suspension feeding in mysticetes represents an evolutionary novelty with no parallel in any other mammalian or known synapsid lineage 15 . Moreover, the innovation of baleen preceded the origin of extremely large body sizes in mysticetes 16 , which rank among the largest vertebrates ever.Although mysticetes use several different modes of filter feeding 3 , rorquals exclusively engulf large volumes of prey-laden water in a single, rapid gulp 4 . In fin whales (Balaenoptera physalus), for example, the entire process of a lunge occurs in a short time span (,6 s), during which approximately 60-80 m 3 of water and prey are engulfed, a volume equal to or greater than that of the individual rorqual itself 17 (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ventrolaterally, the basilar part extends forming a prominent and thick basioccipital crest with a slightly eroded convex surface. Basioccipital crest is long and bulbous, mediolaterally and dorsoventrally thickened, as in all mysticetes (Fitzgerald, 2010). The crest curves laterally in a right angle at the level of the postglenoid process.…”
Section: Descriptionmentioning
confidence: 92%
“…Ventrally, the paroccipital process in the exoccipital is thick (~30 mm anterposterioly) and is exposed posteroventrally. Apparently, its surface has a broad attachment area for the abductor digastric muscle (see El Adli and Fitzgerald, 2010). It is smooth medially and becomes flat to slightly convex dorsally.…”
Section: Descriptionmentioning
confidence: 99%